Policing democracy: overcoming obstacles to citizen security in Latin America - Ungar, Mark (Latin American Studies, 2011)
Realms of change and obstacles to citizen security reform -- Citizen security and democracy -- Honduras -- Bolivia -- Argentina -- Overcoming obstacles to reform.